Ahlback’s disease: Spontaneous osteonecrosis of the Knee - Joshi, Amit; Kayasth, Nirab; Sinha, Ritesh; Singh, Bharat Prasad (Medical Journal of Shree Birendra Hospital, 2015)
Ahlbäck disease is a clinical syndrome characterized by bone necrosis of a load-bearing portion of the femoral condyle, followed by subchondral fracture, subsequent segmental collapse and arthrosis. The diagnosis of the Ahlbäck disease is challenging as sometimes it mimics infection and receives treatment for long time. We report a case of 36 year old gentleman, who presented with confusing radiological picture.